D2.3 Gap analysis - Loureiro, S. M. C. (2022)
Online tool to analyse gaps in the operation of the service provider versus tourist expectations and benchmarks. These months from the beginning of the project until October 2022 have been dedicated to the process of conducting the literature review, using a systematic and bibliometric approach. The objective of this task of conducting the literature review is to get information from scientific articles about dimensions, facets and scales to measure service quality and satisfaction. This step is important to start to develop the tools, namely: satisfaction index and quality index. Tourists who will be the customers of the SMEs involved in the Resetting project are the target to develop these tools. SMEs will benefit in receiving the feedback about the service quality and satisfaction of the service that they offer. The functionality of this tool is to allow SMEs to understand how their customers evaluate the service provide and prepare actions to further improve the service. So, SMEs will use the tool to analyse what they are doing and be able to respond to customers continuously improving what they are doing.